Construction of the Enterococcal Strain Expressing Immunogenic Fragment of SARS-Cov-2 Virus - Suvorov, Alexander; Gupalova, Tatiana; Desheva, Yulia; Kramskaya, Tatiana; Bormotova, Elena; Koroleva, Irina; Kopteva, Olga; Leontieva, Galina (Frontiers in Pharmacology, 2022)
Contemporary SARS-Cov-2 pandemic, besides its dramatic global influence on the human race including health care systems, economies, and political decisions, opened a window for the global experiment with human vaccination employing novel injectable vaccines providing predominantly specific IgG response with little knowledge of their impact on the mucosal immunity. However, it is widely accepted that protection against the pathogens at the gates of the infection - on mucosal surfaces—predominantly rely on an IgA response. Some genetically modified bacteria, including probiotics, represent attractive vehicles for oral or nasal mucosal delivery of therapeutic molecules. Probiotic-based vaccines for mucous membranes are easy to produce in large quantities; they have low cost, provide quite a long T-cell memory, and gut IgA response to oral vaccines is highly synchronized and strongly oligoclonal. Here we present a study demonstrating construction of the novel SARS-Cov-2 vaccine candidate employing the gene fragment of S1 SARS-Cov-2 gene. This DNA fragment was inserted in frame into major pili protein gene with d2 domain of enterococcal operon encoding for pili. The DNA sequencing proved the presence of the insert in enterococcal genome. RNA transcription, immunoprecipitation, and immune electron microscopy with human sera obtained from the SARS-Cov-2 patients demonstrated expression of SARS-Cov-2 antigens in bacteria. Taken together the data obtained allowed considering this genetically modified probiotic strain as an interesting candidate for vaccine against SARS-Cov-2.